2018
DOI: 10.1159/000490216
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Attenuates Myocardial Ischemia/Reperfusion Injury Through Activation of SIRT1 Signaling

Abstract: Background/Aims: Myocardial ischemia/reperfusion (MI/R) injury is a leading factor responsible for damage in myocardial infarction, resulting in additional injury to cardiac tissues involved in oxidative stress, inflammation, and apoptosis. Thymoquinone (TQ), the main constituent of Nigella sativa L. seeds, has been reported to possess various biological activities. However, few reports regarding myocardial protection are available at present. Therefore, this study was conducted aiming to investigate the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…During subsequent experimentation, we further uncovered that SIRT1 inhibited ferroptosis-induced myocardial cell death through the p53/SLC7A11 axis. This is noteworthy as one previous study revealed that TQ confers protection against MI/R injury through activation of the SIRT1 signaling pathway to reduce mitochondrial oxidative stress damage and cardiomyocyte apoptosis by inhibiting p53 acetylation (Lu et al, 2018). Furthermore, another study also proposed that p53 (especially acetylation-defective mutant p53) positively regulates ferroptosis FIGURE 6 | Mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…During subsequent experimentation, we further uncovered that SIRT1 inhibited ferroptosis-induced myocardial cell death through the p53/SLC7A11 axis. This is noteworthy as one previous study revealed that TQ confers protection against MI/R injury through activation of the SIRT1 signaling pathway to reduce mitochondrial oxidative stress damage and cardiomyocyte apoptosis by inhibiting p53 acetylation (Lu et al, 2018). Furthermore, another study also proposed that p53 (especially acetylation-defective mutant p53) positively regulates ferroptosis FIGURE 6 | Mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…One mechanism of TQ may be that it enhances the expression of endothelial nitric oxide synthase and increases nitric oxide levels, potent antioxidant which reacts with toxic molecular radicals, along with down-regulated nitric oxide synthase expression (25). TQ may have improved effects on endoplasmic stress and mitochondrial dysfunction and anti-apoptotic effects through activation of autophagy in damaged cells following numerous I/R models (13,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt/mTOR pathway was found to be activated by the aforementioned natural products, except for thymoquinone and polydatin, which needs further investigation. Another study 196 suggested that thymoquinone mitigated myocardial I/R injury by promoting the activation of SIRT1 and AMPK in this process, although autophagy was not directly explored. As for Danshen extracts, salvianolic acid B 169 and salvianic acid A (danshensu), 170 autophagy initiation was inhibited while autophagic flux was increased by salvianic acid A, as evidence by reduced p62 level and increased formation of autolysosomes.…”
Section: Natural Products That Modulate Autophagy In Cardiac Diseasesmentioning
confidence: 99%